Learner analysis framework for globalized e-learning: A case study - Mamta Saxena (Athabasca University Press, 2011)
The shift to technology-mediated modes of instructional delivery and increased global connectivity has led to the rise in globalized e-learning programs. Educational institutions face multiple challenges as they seek to design effective, engaging, and culturally competent instruction for an increasingly diverse learner population. The purpose of this study was to explore strategies for expanding learner analysis within the instructional design process to better address cultural influences on learning. A case study approach leveraged the experience of practicing instructional designers to build a framework for culturally competent learner analysis.